Underpricing Anomaly and Aftermarket Liquidity of IPOs: An Application on Indonesia Stock Exchange during The Covid 19 Period - Nuraini Desty Nurmasari; Ninditya Nareswari; Novita Rahayu Pratiwi (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2023)
Underpricing occurs when the initial public offering price is lower than the stock's closing price on the first day in the secondary market. This study investigates the influence of IPO pricing and ownership retention against underpricing levels in Initial Public Offering at the Indonesia Stock Exchange (IDX). This study also examines the impact of IPO's underpricing on the aftermarket liquidity based on 167 qualified initial public offerings listed at the Indonesia Stock Exchange during the four years from 2019 to 2022. The proxy used to measure underpricing are initial return and market-adjusted abnormal return. This research uses 167 companies as samples. The sampling technique is purposive sampling. The result shows that the IPO pricing influenced the underpricing levels. The results prove that underpricing gets higher when the IPO pricing is closer to the upper limit of the price range offer. Meanwhile, ownership retention does not affect the underpricing level. The paper also found that IPO underpricing influenced the aftermarket liquidity in two periods: 7 and 30 days after the initial public offering.